Artificial photosynthesis by light absorption, charge separation, and multielectron catalysis - Đokić, Miloš (2018)
Our society’s current energy demands are largely met by the exploitation of fossil fuels, which are unsustainable and environmentally harmful resources. However, Nature has provided us with a clean and virtually limitless alternative in the form of solar energy. This abundant resource is utilized constantly by photosynthetic organisms, which has in turn motivated decades of research in our quest to create artificial counterparts of comparable scales. In this Feature article, we will highlight some of the recent novel approaches in the field of artificial photosynthesis (AP), which we define by a more general term as a process that stores energy overall by generating fuels and chemicals using light. We will particularly emphasize on the potential of a highly modular plug-and-play concept that we hope will persuade the community to explore a more inclusive variety of multielectron redox catalysis to complement the proton reduction and water oxidation half-reactions in traditional solar water splitting systems. We discuss some of the latest developments in the vital functions of light harvesting, charge separation, and multielectron reductive and oxidative catalysis, as well as their optimization, to achieve the ultimate goal of storing sunlight in chemical bonds. Specific attention is dedicated to the use of earth-abundant elements and molecular catalysts that offer greater product selectivity and more intricate control over the reactivity than heterogeneous systems. In this context, we showcase our team’s contributions in presenting a unique oxidative carbon-carbon bond cleavage reaction in aliphatic alcohols and biomass model compounds, under ambient atmospheric conditions, facilitated by vanadium photocatalysts. We offer this discovery as a promising alternative to water oxidation in an integrated AP system, which would concurrently generate both solar fuels and valuable solar chemicals.